2021
DOI: 10.3390/ijerph18084322
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Spatial Safety and Social Psychological Health Features of Deaf Children and Children with an Intellectual Disability in the Public School Environment Based on the Visual Access and Exposure (VAE) Model

Abstract: Nowadays, there is increasing attention towards the safety and feelings of children in urban or architectural space. In this study, the authors suggest a new approach based on the Visual Access and Exposure (VAE) Model to evaluate the spatial safety and social psychological health features of deaf children and children with an intellectual disability in the public school environment. The authors present a preliminary study of deaf children and children with an intellectual disability in a primary school locate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…These children and their parents report that they need not only the appropriate equipment but also medical facilities that will assist them on a daily basis, facilitate mobility, and adjust to their life [ 34 ]. These needs are acknowledged by other scholars, including Mwathi [ 2 , 3 ], who noted that children living with physical disabilities often must depend on others even after they leave formal education. This indicates that such individuals may not have appropriate access to programs, materials, or equipment that prepares them to live independent lives [ 35 ].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…These children and their parents report that they need not only the appropriate equipment but also medical facilities that will assist them on a daily basis, facilitate mobility, and adjust to their life [ 34 ]. These needs are acknowledged by other scholars, including Mwathi [ 2 , 3 ], who noted that children living with physical disabilities often must depend on others even after they leave formal education. This indicates that such individuals may not have appropriate access to programs, materials, or equipment that prepares them to live independent lives [ 35 ].…”
Section: Discussionmentioning
confidence: 96%
“…In contrast to non-disabled children, those with physical disabilities often require more attention, especially when play is used to improve holistic development. Mwathi [ 2 , 3 ] notes that children with physical disabilities often depend on their immediate support network and may participate only minimally within and outside of school. This may be because children with physical disabilities lack appropriate play and learning materials.…”
Section: Introductionmentioning
confidence: 99%
“…Some previous studies had shown that children’s health statuses were compromised by poor housing [ 39 ]. A study among deaf children and children with an intellectual disability in China showed that long corridors and elevators with spaces behind them are not very safe [ 40 ]. However, no studies have discussed the relationship between elevator breakdowns and the health statuses of the children from migrant families.…”
Section: Discussionmentioning
confidence: 99%
“…Using a sample of high schools in New Jersey, USA, Aggarwal J compared data to find a stratified relationship between schools (buildings and facilities) and potential gun violence harborage, noting the need for timely response mechanisms between schools and government [32]. Further, Ning Ma of the Beijing University of Technology, China, designed a safety assessment method for the visually impaired based on the Visual Access and Exposure model of the outdoor campus environment, providing guidance for design and optimization [33]. As can be seen, although there has been some empirical research on school violence prevention through environmental design, it is mostly qualitative research and practice.…”
Section: Introductionmentioning
confidence: 99%